BUILDING ENTREPRENEURSHIP THROUGH TALIKUR CRAFT TRAINING FOR HOUSEHOLD ISSUES - Wahidin (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Talikur craft is currently being favored by women, be it teenagers or adult women. However, not everyone can buy it due to economic limitations considering the price is not cheap. Therefore, this service activity was carried out to provide training on how to make talikur crafts. So, participants can make their own talikur craft as desired. The methods used in this activity are direct training (lectures, demonstrations, and questions and answers) and mentoring. The result of this service is that participants have the knowledge and skills to make talikur crafts in various forms and models.